Título Padrão - Ribeiro, Carolina Maria Ferreira; Salcedo, Diego Andres (Informação em Pauta, 2022)
It presents the final result of the research developed within the METIC Group (formerly Imago and Digital Humanities), linked to the Department of Information Science at the Federal University of Pernambuco. Its objective was to compare Brazilian philatelic collecting practices through social networks and digital social media on the Internet. With an exploratory nature, the research used as a methodological procedure the bibliographical and documental review of the specialized literature in the fields of Library Science, Material Culture and Philately. Three social networks on the Internet (Facebook, Instagram and Twitter) and 1 niche social network on the Internet (Spotify), used by philatelic collectors in Brazil, were identified and selected. The research characterized and compared the sample data. He concluded that philatelic collecting is also digital, while it contributes to the understanding of the use of digital social media and networks on the Internet by philatelic collectors. In addition, he pointed out these digital environments as a locus of memory preservation, of interpersonal and institutional connection, of the relationship between collectible and interacting objects and, finally, of resignification of actions involving the collection of stamps and postal documents.